NUMERICAL MODEL OF A CRYSTAL CLOUD FOR INVESTIGATING BASIC CHARACTERISTICS OF SINGLE SCATTERING - Olga V. Shefer; Victor A. Sennikov (Известия Томского политехнического университета: Промышленная кибернетика, 2023)
A numerical model of a crystalline cloud is proposed for calculating the coefficients of attenuation, scattering, absorption, and single-scattering albedo. A polydisperse medium is represented by a system of spherical particles and an ensemble of predominantly oriented plates. The characteristics of single scattering were calculated within the framework of the Mie theory and the method of physical optics. The features of the spectral behavior of the optical characteristics are demonstrated with a change in the microphysical and optical parameters of the medium.